Natural convection of diamagnetic fluid in an enclosure filled with porous medium under magnetic field. (20th February 2009) - Zeng, Min; Wang, Qiuwang; Ozoe, Hiroyuki; Wang, Gang; Huang, Zipeng
Natural convection in an enclosure filled with a diamagnetic fluid-saturated porous medium under strong magnetic field is numerically investigated. The Brinkman-Forchheimer extended Darcy model is used to solve the momentum equations, and the energy equations for fluid and solid are solved with the Local Thermal Non-Equilibrium (LTNE) model. Computations are performed for a range of Darcy number from 10−6 to 10−3, Rayleigh number from 103 to 106, and magnetic force parameter γ from −200 to 0. The results show that the magnetic force has significant effect on the flow field and heat transfer in a diamagnetic fluid-saturated porous medium.